Skin Delivery of siRNA Using Sponge Spicules in Combination with Cationic Flexible Liposomes - XueJiao Liang; JiaLiang Zhang; HuiLong Ou; Jun Chen; Samir Mitragotri; Ming Chen (Elsevier, 2020)
We report the topical administration of sponge Haliclona sp. Spicules (SHS) combined with cationic flexible liposomes (CFL) to increase the delivery of small interfering RNA (siRNA) into viable skin cells in vitro and in vivo. SHS can be applied topically as novel microneedles to overcome skin barrier by creating plenty of new microchannels in stratum corneum. Subsequently, well-designed CFL can be also utilized topically as nanocarriers to overcome skin cells membrane by delivering siRNA to skin deep layers through these microchannels and thereby facilitating their cell internalization. The topical application of SHS in combination with CFL (0.05% of lipids, w/v), referred to as CFL(0.05%), enhanced siRNA skin penetration in vitro by 72.95 ± 2.97-fold compared to control group (p < 0.001). Further, the topical application of SHS in combination with CFL(0.05%) on female BALB/c mice skin resulted in 29.21% ± 1.41% of glyceraldehyde-3-phosphate dehydrogenase (GAPDH) knockdown at all application area in vivo, which was not significantly different from the GAPDH protein knockdown rate in the subcutaneous injection center. However, the high knockdown rate only appears in the vicinity (<0.5 cm) of the injection center. In sum, this study provides a promising strategy of topical delivery of siRNA by the combined used of SHS and well-designed CFL.